Mother Tongue as a Threat for English Language Learning at Primary Level in Indian Schools: a Survey-Based Study - Kumar, Tribhuwan; Ritonga, Mahyudin; Julhadi, Julhadi (SCAD Independent, 2022)
This study looked at the possibility of using the mother tongue (MT) as an instructional tool at the elementary level of schooling in India. Many academics have remained intent on using their native languages as a medium of teaching in elementary schools because of the country's multilingual character. This study explained why MT, as an instructional tool, may or may not be successful in the coming years, and many issues that make it impossible to carry out are also discussed. Through a purposeful sampling method, the researcher gathered data from 150 elementary school teachers from government-run and private schools in the western part of Uttar Pradesh, India. To gather data, the researcher needed a well-designed questionnaire consisting of questions in two parts- Part A and Part B. The first part wanted demographic data on respondents. In contrast, the second part focused on the many reasons that encourage or discourage primary school students in India from learning their native language. Alpha, mean, and standard deviation were used to evaluate the data obtained. Using MT as an instructional tool in Indian elementary education, the multilingual character of India, and the unavailability of instructional material and scientific equipment in indigenous languages constitute hindrances.